Mobile health applications for the management of primary hypertension: A multicenter, randomized, controlled trial. Issue 16 (April 2020) - Gong, Ke; Yan, Yu-Ling; Li, Yu; Du, Jun; Wang, Jing; Han, Yue; Zou, Ya; Zou, Xin-yu; Huang, Hong; She, Qiang
Abstract: Background: Hypertension is 1 of the major global public health challenges, which means that patients with hypertension need more measures to control their blood pressure. Currently, smart phones and applications are developing rapidly, and mobile health applications are used to manage hypertension, but evidences related to effectiveness are limited. Objective: The purpose was to assess the impact of m-Health apps on blood pressure control, medication adherence. Methods: 480 participants were randomly assigned to the intervention and control groups. The intervention group used the "Yan Fu" app to manage their blood pressure, and the control group did not use any m-Health apps. The outcomes were changes in blood pressure, the percentage of participants with their blood pressure under control and medication adherence. Results: At the end of the study, the baseline characteristics between the 2 groups had no statistically differences ( P > .05). Participants in the 2 groups all had lower systolic blood pressure and diastolic blood pressure than they did at baseline, and the intervention group demonstrated a significantly greater systolic blood pressure and diastolic blood pressure reduction than the control group ( P < .05). Additionally, the percentage of participants with controlled blood pressure was higher in the intervention group ( P < .05). The medication adherence of the intervention group was much higher than that of the control group ( P < .05). Conclusion: M-Health apps are effective for hypertension management, it can favor the medication adherence and blood pressure control. Perhaps m-Health apps can be promoted in the blood pressure control. Trial Registration: This study was registered in the Chinese Clinical Trial Registry under the number ChiCTR-IOR-17012069.